Studi Perbandingan Kebijakan Pangan Fungsional di Indonesia dan Beberapa Negara Lainnya - Prakoso Bhairawa Putera (Inovasi, 2020)
This paper aims to provide an overview of how changes in regulations related to functional food and the comparison of food arrangements in several other countries, especially in functional or claimed food, and to figure out future challenges for the regulation of functional food. The research method used is qualitative and the data used are primary and secondary data. The results shows that some countries specifically regulate functional food. The challenges faced for functional food development are regulation, institutional, database, and exploration and identification of functional food sources from the sea. Keywords: functional food, claimed, comparation, regulation, challenges